PENARIKAN BARANG YANG MENJADI OBYEK SEWA BELI DALAM HAL PEMBELI SEWA WANPRESTASI - Sumiasi, Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 3 (2013), 2013)
The article entitled The Withdrawal of the Leasing Object in the event of Customer’s Default in Payment. The main issue discussed is that whether the withdrawal of the leasing object is acceptable by the law in the event of customer’s default in payment. The research in this paper is classified as a Normative Legal research, which is based on primary and secondary legal materials. The approach taken was the statutory and the analytical conceptual approach. The research results indicate that with the withdrawal of leasing object in a lease agreement by the creditor according to law (under the provisions of Article 1338 of Indonesian Civil Code) can be justified and lawful. The agreement of waiving the provisions of article 1266 of paragraph 2 of Indonesian Civil Code binding on the partie based on the principle of freedom of contract
Keywords: Withdrawal of leasing goods; Leasing; Default